The Financing and Growth of Firms in China and India : Evidence from Capital Markets - Didier, Tatiana; Schmukler, Sergio L. (Elsevier, 2013)
This paper studies the extent to which firms in China and India use capital markets to obtain financing and grow. Using new data on domestic and international capital raising and firm performance, it finds that financial market activity has expanded less since the 1990s than aggregate figures suggest. Relatively few firms raise capital and even fewer attract most of the financing. Moreover, firms that issue equity or bonds are different and behave differently from other publicly listed firms. Among other things, they are typically larger and grow faster. The differences between users and nonusers exist before the capital raising, are associated with the probability of raising capital, and become more pronounced afterward. The size distribution of issuing firms shifts more over time than the distribution of those that do not issue, suggesting little convergence in size among listed firms.